2021
DOI: 10.1080/13880209.2021.1979051
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of Tangwang Mingmu granule for the management of diabetic retinopathy based on network pharmacology

Abstract: Context Tangwang Mingmu granule (TWMM), a traditional Chinese medicine, has been widely used in the treatment of diabetic retinopathy (DR), the most common microvascular complication in diabetes mellitus. Objective To establish a method to select target compounds from herbs for a pharmacokinetic study using network pharmacology, which could be applied in clinical settings. Materials and methods First, UPLC/Q Exactive Q-Orbitrap and GCMS 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Furthermore, el-Remessy AB et al proposed that 45 high glucose treatment blocks the pro-survival effect of VEGF and causes accelerated endothelial cell apoptosis via the action of peroxynitrite in causing tyrosine nitration of PI 3-kinase, so as to inhibit activity of Akt-1 kinase and increasing the activity of p38 MAP kinase. In addition, Wang et al also pointed out that 46 MAPK14 was identified gene candidate of potentially involved in DR, which was consistent with the results of this study. Saik OV etc.…”
Section: Constructionsupporting
confidence: 92%
“…Furthermore, el-Remessy AB et al proposed that 45 high glucose treatment blocks the pro-survival effect of VEGF and causes accelerated endothelial cell apoptosis via the action of peroxynitrite in causing tyrosine nitration of PI 3-kinase, so as to inhibit activity of Akt-1 kinase and increasing the activity of p38 MAP kinase. In addition, Wang et al also pointed out that 46 MAPK14 was identified gene candidate of potentially involved in DR, which was consistent with the results of this study. Saik OV etc.…”
Section: Constructionsupporting
confidence: 92%
“…Tangwang Mingmu granule is a traditional Chinese medicine, which has been widely applied in the DR treatment. Wang et al 9 performed a pharmacokinetic study and found that STA was the main compound of Tangwang Mingmu granule. This aroused our interest to explore whether STA can play a therapeutic effect on DR?…”
Section: Discussionmentioning
confidence: 99%
“… 8 Autophagy is a double-edged sword in the growth process of eukaryotic cells, which runs through the normal growth, proliferation, and pathophysiological process. 9 For example, in the physiological state or at the early stage of some diseases, autophagy helps to clear senescent and damaged cells or organelles, while when autophagy is too strong, it has a pathogenic effect on cells, tissues, and organs. 10 Recently, many researches demonstrated that activating autophagy might be a promising therapeutic strategy in DR. 11 , 12 Adenosine monophosphate-activated protein kinase (AMPK) participates in the regulation of energy metabolism, plays a protective role in many diseases including DR. 13 Sirtuin 1 (SIRT1), one of the sirtuins family members, is a nicotinamide adenine dinucleotide (NAD +)-dependent histone deacetylase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Network pharmacology is an emerging research approach combined with pharmacology, bioinformatics, and network biology (Lin et al, 2022). The compound-target-pathway networks can be predicted the biologically active ingredients and elaborate the compound mechanism of action (Wang et al, 2021). Today, network pharmacology comprehensively and systematically reveals the active ingredients (Jian et al, 2022) and potential mechanisms of action of TCM preparations by integrating multiple networks…”
Section: Introductionmentioning
confidence: 99%